MENINGKATKAN KECERDASAN LOGIKA MATEMATIKA MELALUI KEGIATAN FUN COOKING (Penelitian Tindakan pada Anak Kelompok B2 di TK Negeri Pembina Pandeglang) - Desri Yanti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
This research aims to improve children’s intelligence mathematical logic B2 group through fun cooking activities in TK Negeri Pembina Pandeglang year 2015/2016. The subjects were children in group B2 consisting of 15 children: nine girls and six boys. This research was conducted in TK Negeri Pembina Pandeglang located on the street perkantoran Cikupa No. 2 Pandeglang Banten. The method used is action research conducted through two cycles, the first cycle consists of eight actions and the second cycle consists of two measures. Cycle consists of planning, action, observation and reflection. The instrument used in this study is the observation, field notes, interviews, and documentation notes. The results obtained in mathematical logic intelligence pre-research children 36%. Once the child is given the action on the first cycle, logical-mathematical intelligence of children increased to 67%, the second cycle was obtained a yield of 79%. Thus, logical-mathematical intelligence of children has increased and is at the level of developing very well. It can be concluded that by using fun cooking activity can increase intelligence in children mathematical logic B2 group in TK Negeri Pembina Pandeglang.